Manajemen Guru sebagai Upaya Pencapaian Visi-Misi Sekolah (Studi di Sekolah Menengah Atas Persatuan Guru Islam Indonesia 1 Kota Bandung) - Ali Makhrus; Rizki Amalia (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2019)
The development of technology demands Islamic education institution as the actor of islamization of knowledge project to increase its quality through management of teachers. As the key for achieving school’s vision, teachers must be managed well. This research investigated the process of management of teachers conducted by SMA PGII 1 Bandung. This school was chosen since it evidently could achieve its vision and have competitive alumna showen by their success in getting scholarschip to Germany. This was a case study with qualitative approach. The instruments were interview, questionnaire and observation with teacher, vice of headmaster and chief of administration as respondents. The results show that this school has serious efforts in protect the teachers’ professionalism since recruitment process. The founding program, performance analysis, giving appreciation and sanction become the strategies in increasing the teachers’ quality. This shows that by a comprehensive management of teachers, a school could achieve its vision.